Observation of quantum Hall effect in a microstrained Bi2Se3 single crystal. (April 2017) - Kumar, Devendra; Lakhani, Archana
Abstract : Graphical abstract: Abstract : Highlights: Bi2 Se3 single crystal is characterized by HRXRD, SEM, and transport measurements. The crystal shows the presence of lattice disorder which causes microstrain. Quantum Hall plateaus are observed at the minima of SdH oscillations. The observed quantum Hall effect (QHE) has the bulk origin. Our results suggest that perfect 2D transport is not essential for QHE in Bi2 Se3 . Abstract: We report the observation of quantum Hall effect (QHE) in a Bi2 Se3 single crystal having carrier concentration ( n ) ∼ 1.13 × 10 19  cm −3, three dimensional Fermi surface and bulk transport characteristics. The plateaus in Hall resistivity coincide with minima of Shubnikov de Haas oscillations in resistivity. Our results demonstrate that the presence of perfect two dimensional transport is not an essential condition for QHE in Bi2 Se3 . The results of high resolution X-ray diffraction (HRXRD), energy-dispersive X-ray spectroscopy (EDX), and residual resistivity measurements show the presence of enhanced crystalline defects and microstrain. We discuss the possible origin of the observed QHE and correlate its existence to the crystalline defects.